Transition-metal-free Baeyer–Villiger oxidation of benzaldehydes to phenols using Na2S2O8. Issue 3 (March 2019) - Li, Wei; Chen, Lin-Lin; Han, Ke; Liu, Zhi-Bin; Luan, You-Shun; Chen, Deng-Tai
A new approach for preparation of phenols from benzaldehydes using Na2 S2 O8 has been established. This reaction is a Na2 S2 O8 -promoted Baeyer–Villiger oxidation. It provides a highly efficient and practical approach for the preparation of phenols. The protocol is highlighted by its operational simplicity and mild conditions.